2014
DOI: 10.1159/000356892
|View full text |Cite
|
Sign up to set email alerts
|

A Relatively High Number of Pregnant Women in Kuwait Remain Susceptible to Rubella: A Need for an Alternative Vaccination Policy

Abstract: Objective: To measure the prevalence of anti-rubella IgG and hepatitis B surface antigen (HBsAg) among pregnant women in Kuwait in order to assess the effectiveness of the current vaccination programs. Subjects and Methods: This retrospective study involved 4,062 pregnant women evaluated in health centers in the Hawalli Province of Kuwait. They were screened for anti-rubella IgG and HBsAg using commercially available assays. The data were obtained from medical laboratory records. Results: The mean age of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…We identified over 220 studies that provided cross‐sectional data and nearly 180 studies that reported on immunity for women of child‐bearing age, primarily for rubella. Table summarizes the over 400 cross‐sectional and women of child‐bearing age measles and rubella serological studies…”
Section: Resultsmentioning
confidence: 99%
“…We identified over 220 studies that provided cross‐sectional data and nearly 180 studies that reported on immunity for women of child‐bearing age, primarily for rubella. Table summarizes the over 400 cross‐sectional and women of child‐bearing age measles and rubella serological studies…”
Section: Resultsmentioning
confidence: 99%
“…1,4,13 However, the seroprevalence of rubella immunity in the current study was higher than findings from other countries like southern India (65%), Niger (53%), and lower than findings from Nigeria (97.9%), Mexico (97.1%), Turkey (96.1%), Spain (94.1%), Western Province in KSA (91.6%), Cameroon (88.6%) and Kuwait (88.4%). 1,3,14,15 The differences in seroprevalence between different studies could be attributed to the variation in the epidemiology of the infection, the differences in the sample size and the methodology of the studies, the utilised laboratory tests, discrepancies in the used cut-off points used to confirm the immunity, and the involvement of rubella immunisation in their national vaccination programs. 1,16 There were no significant variations in antenatal characteristics of patients between susceptible and immune groups.…”
Section: Discussionmentioning
confidence: 99%
“…A study done in 2012-2013 in 4062 pregnant females in the Hawalli Province in Kuwait found 0.3% HBsAg positivity [35].…”
Section: Central Asia (Afghanistan Kazakhstan Kyrgyzstan Tajikistan T...mentioning
confidence: 98%